Bone marrow megakaryocytes, soluble P-selectin and thrombopoietic cytokines in multiple myeloma patients. (May 2014) - Lemancewicz, Dorota; Bolkun, Lukasz; Mantur, Maria; Semeniuk, Janusz; Kloczko, Janusz; Dzieciol, Janusz
Abstract The expression of adhesion molecules and other cell-surface molecules is substantial in the communication between plasma cells and bone marrow microenvironment, and may lead to increased proliferation of myeloma cells. Many of the cytokines involved in multiple myeloma (MM) pathogenesis, e.g. thrombopoietin (TPO) and interleukin-6 (IL-6), play a pivotal role in different developmental stages of megakaryocytopoiesis and thrombopoiesis. The principal aim of our study was to explore the relationship between thrombopoietic cytokines, megakaryocytes (MKs) and soluble P-selectin (sP-selectin) levels in MM patients before and after anti-angiogenic treatment. Forty-four patients (20 female and 24 male) with a newly diagnosed MM were examined in three groups, following a division based on the International Staging System, ISS. Plasma levels of TPO, IL-6 and soluble P-selectin (human sP-selectin) were measured by means of ELISA. Bone marrow specimens were studied to determine the number of MKs and the so-called "naked nuclei" (NN), as well as the expression of platelet-derived growth factor (PDGF). The comparison revealed a significantly higher concentration of cytokines and sP-selectin in newly diagnosed MM patients compared to healthy volunteers: for TPO, p = 0.01, IL-6, p = 0.0005 and sP-selectin, p = 0.00008, respectively. Marked differences were observed in the concentration of sP-selectin, expression of PDGF and MKs counts between patients with MM stage I and MM stage III. Statistically meaningful correspondences were also found between MKs versus TPO, NN versus TPO, as well as MKs versus MPV, p = 0.009, p = 0.004 and p = 0.0005, respectively. Furthermore, the analysis exhibited some statistically meaningful divergences between initial concentrations of sP-selectin in subgroups with different response after chemotherapy. The initial concentration of sP-selectin in the group of MM patients with complete or partial remission stood at 31.86 ± 6.13 ng/ml. In the remaining patients (stable disease), the concentration of sP-selectin amounted to 35.15 ± 7.23 ng/ml (p = 0.048). We found a correlation between sP-selectin and IL-6 (ρ = 0.57, p = 0.0004), TPO and IL-6 (ρ = 0.46, p = 0.001) as well as sP-selectin and TPO (ρ = 0.36, p = 0.043), and sP-selectin and PDGF (ρ = 0.36, p = 0.03). Our study has eventually demonstrated that sP-selectin, as a marker of platelet activation, could be a useful marker of maximum response to therapy. Its strong association with another marker like PDGF-AB could further lead to the development of new combinational therapeutic strategies of anti-angiogenic therapy in MM patients.